KEABSAHAN TINDAKAN MENURUNKAN STATUS PERKARA PENYIDIKAN OLEH POLDA BANGKA BELITUNG TERHADAP LAPORAN POLISI NOMOR: LP/3388/VII/2016/PMJ/DITRESKRIMSUS - Rio Kurniawan; Ade Adhari (Jurnal Hukum Adigama, 2022)
Criminal procedural law regulates the proceedings with all existing authorities in accordance with written procedures, this is in accordance with lex scripta which means that everything carried out in the investigation and investigation process must be in accordance with the Regulation of the Head of the Indonesian National Police Number 6 of 2019 in article t. -10 regarding the process of investigating criminal acts. This raises in the discussion of this research case, which has a problem regarding how the validity of the act of reducing the status of the investigation case to an investigation by the Bangka Belitung Police against Police Report Number: LP 3388/VII/2016/PMJ/DITRESKRIMSUS? This study uses a deductive research method that relies on theories as a research tool in presenting the results of the analysis in the form of a qualitative descriptive objective assessment in order to answer the problems in the research. The results of the study indicate that the act of delegating is legally valid based on Presidential Regulation Number 52 of 2010 concerning Organizational Structure and State Work Procedures of the Republic of Indonesia accompanied by opinions and quotes collected from experts in criminal procedural law, it can be said that Polda Metro Jaya and Polda Bangka Belitung have equal authority and rights to carry out an investigation/investigation of a criminal case, so the views and decisions of each investigation must be carried out.